Nuovi strumenti di Telerilevamento da satellite per il controllo del territorio - Dussi, Michele (GEOmedia, 2008)
New instruments for land management utilizing satellite remote sensing We are at the beginning of a new Earth Observation age comprised of large amounts of data, high revisit times as well as high resolution images. All these characteristics were "dream-requirements” for E.O. operators in the past years. Today a new solution dubbed Cosmo-Skymed is being developed which will be operational in the coming months. Cosmo-Skymed is a dual-use end-to-end global data providing system. It makes use of an innovative constellation of 4 sun-synchronous satellites equipped with multimodal high-res synthetic aperture radar (SAR). It operates in X-band and is supported by a wide G/S infrastructure to meet high performance data acquisition and distribution service requirements. It is a made in Italy solution.